2010
DOI: 10.1126/science.1190721
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Control Breathing Through pH-Dependent Release of ATP

Abstract: Astrocytes provide structural and metabolic support for neuronal networks, but direct evidence demonstrating their active role in complex behaviors is limited. Central respiratory chemosensitivity is an essential mechanism which, via regulation of breathing, maintains constant levels of blood and brain PCO 2 /pH. We found that astrocytes of the brainstem chemoreceptor areas are highly chemosensitive. They responded to physiological decreases in pH with vigorous elevations in intracellular Ca 2+ and release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
900
4
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 770 publications
(943 citation statements)
references
References 28 publications
26
900
4
13
Order By: Relevance
“…2002, 2015; Gourine et al . 2010), because metabolic changes in response to local heating and cooling are relatively small (Barcroft & Edholm, 1943; Pearson et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2002, 2015; Gourine et al . 2010), because metabolic changes in response to local heating and cooling are relatively small (Barcroft & Edholm, 1943; Pearson et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with this work, Gourine and colleagues have examined the sensitivity of astrocytes of the VMS to pH [52]. They have demonstrated that changes in pH can evoke Ca 2+ waves in these astrocytes that depend on the prior release of ATP (probably in this case via exocytosis).…”
Section: Co 2 Chemosensory Transductionmentioning
confidence: 93%
“…However, this negative evidence has more recently been overturnedwhen challenged with a CO 2 stimulus in the neonate (as opposed to a pH stimulus), a significant component of the retrotrapezoid neuron responses is indeed ATP receptordependent [51]. At adult stages, the response of these neurons is almost entirely dependent on the prior release of ATP [52]. However, ATP biosensing has had two even more profound consequences for understanding of CO 2 chemosensory mechanisms.…”
Section: Co 2 Chemosensory Transductionmentioning
confidence: 99%
“…sGFAP is a transcriptionally enhanced, bidirectional, shortened glial fibrillary acidic protein promoter which drives transgene expression in astrocytes (Figueiredo et al, 2011; Gourine et al, 2010; Liu, Paton, & Kasparov, 2008). Fusions with EGFP or mKate2.7 allow detection of transgene expression via green or red fluorescence, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Purinoceptors are expressed by astrocytes, and readily respond to the increases in extracellular ATP concentration (Angelova et al, 2015; Coco et al, 2003; Gourine et al, 2010). Regulated exocytosis of signaling molecules by astrocytes may involve different types of secretory organelles (synaptic‐like microvesicles, dense‐core vesicles, lysosomes, exosomes, and ectosomes (Oya et al, 2013; Verkhratsky, Matteoli, Parpura, Mothet, & Zorec, 2016).…”
Section: Introductionmentioning
confidence: 99%